THE EFFECT OF BLOOD DRUG (CHISTOTEL) (CHELIDOII HERBA) AND ALOE EXTRACT ON THE REGENERATIVE PROCESS OF SKIN-MUSCLE INJURIES (Conferencea, 2024)
In this article, an increase in the concentration of collagen, an increase in re-epithelialization, and a faster closure of the wound defect were determined when a 1:3 water solution of blood thorn (chistotel) and aloe extract were used in the treatment of artificially induced wounds in white mice, and the experimental results of their use in the treatment of pathological processes were described.